KREATIVITAS ANAK : PERMAINAN KOMPOSISI SIKAP DAN GERAK TARI (Sebuah Pendekatan Imajinatif melalui Aktivitas Metaforik Berbasis Alam Sekitar Untuk Pembelajaran Seni Tari di Pendidikan Dasar) - Beben Barnas (Universitas Pendidikan Indonesia, 2015)
It is very possible to help students learn how to see and response their environment. Hawkin posits that if one teaches choreography in an experimental class, it is better to use a certain model of observation as a tool to help him perceive the pattern. From the perspective of a teacher about creativity is that it includes all productive efforts which are unique from the individual to help children digging and developing their potency optimally. A teacher has been encountered by an important question: how to create a situation which can help students to build an achievable environment for each individual to response intuitively and attract to move creatively. The lack of confidence in children and environment can complicate and even block the attitude to accept experiences and the encouragement to create a dance movement. A necessity of learning creative dance needs an environmental maintenance which gives freedom to the children to react intuitively without feel scared of judgment (right or wrong) of their creativity. Furthermore, it enables children to be confident. The role of a teacher here is to stimulate students’ creativity by giving some metaphorical expressions so that they can create and develop their own creative movements. Metaphorical activity in encouraging children’s creativity in learning dance is a process of learning which gives a way of working to help its environment. It gives facilities and opportunities to the students to develop their ability. The ability to explore and find dance movement through their potential creativity is expected will give them freedom to experience, find, and create passion -from their heart- in creating variety of dance movements which are appropriate with the purpose of the study which is determined in dance subject in the Elementary Schools.